Validity of honda Philippines' restrictions to use honda cars as public utility vehicles - Morando, Jovit R. (Animo Repository, 2007)
The transportation industry in the country is one of the growing industries in our country. Jeepneys and buses are growing in number to accommodate the increasing number of commuters. In proportion to the increase in number of jeepney and buses is the increase in the number of taxicabs rounding the streets of Metro Manila. Noticeable among the taxi is the common use of brands such as Toyota, Nissan and Mitsubishi. There are some KIA Prides plying the streets of the Metro Manila and some Korean brands. However, absent from the brands is one of the biggest player in the car industry which is Honda. The absence of Honda in the Taxicab industry is primarily due to the restriction imposed by Honda to car owners to use such property as Public Utility Vehicles or taxicabs. According to Honda Philippines, the restriction is imposed for brand protection and image protection purposes. The purpose of this study is to determine the validity of Honda’s restriction to use Honda cars as PUVs. In order to determine the validity of the restriction, the researcher conducted several interviews with legal experts. Several taxi operators were also interviewed along with the riding public. The results showed that the restriction imposed by Honda is not contrary to law, morals, customs, public order or public policy. The provision of the contract between Honda and the buyer becomes the law between the parties as this is not contrary to the Civil Code.